Nail withdrawal of three selected Malaysian timbers / Mohamad Uzair Hazzard Ahmad Zaini - Ahmad Zaini, Mohamad Uzair Hazzard (Faculty of Applied Sciences, 2015)
The study was carried out to determine the right selection of the nail based on the intended purpose while doing nailing process towards Malaysian timber spp and to determine the holding strength properties of nails on the Malaysian timber, spp. also to evaluate the suitability of nail on different category of Malaysian timber spp. that species are Sesenduk (Endospermum Spp), Semarak Api (Delonix Regia, Spp) and Resak (Vatica, Spp). Three samples of each species were produced in size 100mm x 100mm x 100mm with using a common nail. Based on the results of this study it was found that the density of wood affected the withdrawal strength of nailing. That showed in the statistical analyses higher density of species is highly significant. The lowest density of species are suitable use common nail as a fastener in furniture manufacture.